Tantangan Manajemen Layanan Akademik pada Masa Pandemi Covid-19 - Siti Kurniawati; Danny Meirawan (Jurnal Administrasi Pendidikan, 2021)
The study aims to analyse and describe the challenges in managing academic services in college during the Covid-19 pandemic. This study focused on the object of research in the Division of Education Services Education Directorate UPI. The qualitative descriptive method is used as the main method in this research. The data collecting process is conducted through observation and interview with the unit leader of the Education Service Division, the Directorate of Education UPI. The resulting research shows that there are so many challenges that are faced and of course require special problem solving in serving education service users in the midst of the pandemic. The roles of organizational leader are crucial to making the right decision in the face of challenges. Academic services would be effective if each person committed and cooperated in providing the best service to the users. It also would succeed if it was supported by utilizing information technology that can be accessed easily by the services users.